2003
DOI: 10.1063/1.1558594
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic two-dimensional short-range order in hexagonal manganites

Abstract: Hexagonal manganites REMnO3 consist of layers of two-dimensional connected distorted MnO5 bipyramids separated by distorted layers of RE, leading to frustrated Mn3+–O2−–Mn3+ in-plane exchange paths (superexchange) and Mn3+–O2−–O2−–Mn3+ interplane exchange paths (super-superexchange). We report single-crystal diffraction experiments (RE=Ho,Er,Y) indicating magnetic 2D short-range order up to temperatures of T=150 K (TN∼74 K), and SQUID magnetization data (RE=Y) indicating short-range order up to at least 250 K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 13 publications
7
12
0
Order By: Relevance
“…YMnO 3 is a quasi-2D magnetic system. So one expects diffuse scattering rods parallel to c * close to T N Ϸ 70 K. We have, indeed, found such rod scattering above T N , in agreement with the results of Lonkai et al 21 We performed several Q scans perpendicular to the rod across Q = ͑1,0,0.11͒. Fig.…”
Section: Neutron Diffraction Investigationsupporting
confidence: 90%
“…YMnO 3 is a quasi-2D magnetic system. So one expects diffuse scattering rods parallel to c * close to T N Ϸ 70 K. We have, indeed, found such rod scattering above T N , in agreement with the results of Lonkai et al 21 We performed several Q scans perpendicular to the rod across Q = ͑1,0,0.11͒. Fig.…”
Section: Neutron Diffraction Investigationsupporting
confidence: 90%
“…The sharp slope change is consistent with earlier reports for single crystals [144][145][146]. However, the magnetic signature at may be less clear in powder samples, possibly due to sample quality or grain size problems [43,90,95,[147][148][149][150].…”
Section: Magnetoelectric Effects In Hexagonal Manganitessupporting
confidence: 81%
“…The discussion about the magnetic symmetry of YMnO 3 below the Néel temperature is even more complicated after signatures of diffuse scattering as well as unconventional short range spin fluctuations have been reported above as well as in the ordered phase [147,148,[155][156][157]. The results seem to be consistent with a quasi two-dimensional frustrated magnetic system with weak interplane coupling and a spin liquid phase above which extends into the magnetically ordered phase below .…”
Section: Magnetoelectric Effects In Hexagonal Manganitessupporting
confidence: 75%
“…In the case of YMnO 3 , a clear deviation from the CW description was observed at 250 K itself, signifying the presence of spin fluctuations related to a two-dimensional (2D) short-range type. 21 Similarly, in the present frustrated magnet also, a CW description may not be the accurate one. The observed linearity of inverse susceptibility still has a major contribution from the paramagnetic susceptibility of Dy.…”
Section: Magnetizationmentioning
confidence: 69%
“…From the specific heat measurements it is found that the Y dilution enhances O4 are oxygens in the basal plane of the MnO 5 bipyramid). 21 Insertion of nonmagnetic Y atoms between the layers of Mn bipyramids will only weaken the interlayer exchange further. The fact that the T Mn N has increased indicates the importance of the intralayer coupling between Mn in the basal plane.…”
Section: Specific Heatmentioning
confidence: 99%